Far from the core - regions and industrial parks in economic shadow in Hungary (Part one) - Tiner, Tibor (Hungarian Geographical Bulletin, 2010)
The economic development of NUTS2 regions in Hungary can be evaluated in different ways. It is their economic potential which is put in the focus of this paper. This potential can be measured by total revenues of leading companies operating on their territories in the first place, and then by number, profile and profit of these firms settled into industrial parks of the regions. The results of an analysis showing close correlation between their geographical position and success (or failure) in business might be used by the experts of the regional development agencies in decision making. This article is an attempt to evaluate the level of development of NUTS2 regions on the basic data for the leading 500 companies. The second part of the paper (Hung. Geogr. Bull. No 3. 2010) will deal with economic efficiency of top firms which are settled into industrial parks of less favoured regions. Analyses are going on the basis of financial and statistical indicators published by different institutions and firms (e.g. Central Statistical Office, Creditreform Ltd.) electronically or in printed version. The study also deals with a few regional effects of economic crisis burst in 2008.